Funkcje i sposoby stylizacji językowej w XII epizodzie "Ulissesa" - Szczerbowski, Tadeusz (Stylistyka, 1996)
The "Cyclops" episode is a complex intertextual game based on stylistic polyphony. lt abounds in various polemic imitations of almost all styles known in Dublin in 1905. Joyce is critical of their users: the writers of the Celtic Twilight, narrow-minded nationalists; priests, theosophists, lawyers and joumalists. Stylistic contrasts, characteristic of parody, are common in the episode.